Resepsi Politik Perempuan terhadap Program Perempuan Bicara di tvOne - Alifianisa, Safa; Roem, Elva Ronaning; Elian, Novi (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2025)
The study analyzes the meaning that female audiences derive from the Perempuan Bicara program on tvOne, specifically the episode titled "Anies, Prabowo, atau Ganjar? Siapa Bisa Pikat Hati Perempuan." This episode discusses women's participation in the 2024 election, focusing on their readiness to use their voting rights, the perspectives of young voters, and the political engagement of women. The research employs a qualitative approach with data collection methods including interviews, observations, and documentation, involving six informants who are students from the Faculty of Social and Political Sciences at Andalas University. The results show that the meaning derived by female audiences from the program is influenced by the informants' backgrounds and experiences. The female students who participated in the study interpret the messages in the program based on the relevance of the issues discussed to their lives, their interest in politics, and the social contexts they experience. For some informants, the program provides new insights into the importance of women's roles in politics, especially as the 2024 election approaches. They believe that the discussions in this episode strengthen awareness of women's voting rights. However, some informants feel that the discussions are somewhat superficial and lack critical exploration of fundamental issues facing women.